2022
DOI: 10.4300/jgme-d-22-00332.1
|View full text |Cite
|
Sign up to set email alerts
|

Do Lower Costs for Applicants Come at the Expense of Program Perception? A Cross-Sectional Survey Study of Virtual Residency Interviews

Abstract: Background Travel costs and application fees make in-person residency interviews expensive, compounding existing financial burdens on medical students. We hypothesized virtual interviews (VI) would be associated with decreased costs for applicants compared to in-person interviews (IPI) but at the expense of gathering information with which to assess the program. Objective To survey senior medical students and postgraduate yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…Of these, cost and time conflicts have been noted in the literature as significant obstacles when conducting inperson interviews, especially for competitive specialties such as otolaryngology. 2,3,6 Potential solutions proposed include funding away rotations and research experiences, which were found to predict total interview season cost. 2 Additionally, Fogel et al 3 discussed co-locating interviews or adopting a city or regional-based approach for interview dates to lessen travel costs and time conflicts.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Of these, cost and time conflicts have been noted in the literature as significant obstacles when conducting inperson interviews, especially for competitive specialties such as otolaryngology. 2,3,6 Potential solutions proposed include funding away rotations and research experiences, which were found to predict total interview season cost. 2 Additionally, Fogel et al 3 discussed co-locating interviews or adopting a city or regional-based approach for interview dates to lessen travel costs and time conflicts.…”
Section: Discussionmentioning
confidence: 99%
“…The most common reasons for declining an in‐person interview were not wanting to travel, time conflicts, dissatisfaction with the geographic location, and monetary limitations. Of these, cost and time conflicts have been noted in the literature as significant obstacles when conducting in‐person interviews, especially for competitive specialties such as otolaryngology 2,3,6 . Potential solutions proposed include funding away rotations and research experiences, which were found to predict total interview season cost 2 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…2 Studies comparing virtual interviews to historical in-person interview offerings suggest advantages to the virtual format: reduced costs, avoidance of scheduling conflicts, and avoidance of educational interruptions. 3 , 4 , 5 , 6 These benefits, however, occur at the expense of applicant perception of the programs. 6 …”
Section: Introductionmentioning
confidence: 99%